Synchronous monitoring of axial vibration and rotation speed of rotating cylinder by linear array scanning. (1st December 2022) - Deng, Yunnan; He, Zifen; Zhang, Yinhui; Wang, Sen
Highlights: A generalized visual measurement method for synchronous monitoring of the axial vibration and rotation speed via linear array scanning. Method based on gray gradient of row pixels for edge pixel extraction in linear array images. Seam compensation and axial offset correction for elimination of measurement errors due to manual mark pasting. Measurement performance evaluation by experiments at a scanning distance of 500 mm. Abstract: The axial vibration (AV) and rotation speed (RS) signals of a rotating cylinder contain rich condition information. In order to harness such quantitative information, an effective measurement method for synchronous monitoring of the AV and RS is highly desirable. However, traditional approaches are restricted either by limited test distance or multiple isolated sensors, which makes the approaches impractical to synchronously acquire the AV and RS signals through a single device. In this paper, a generalized visual measurement method for synchronous monitoring of the AV and RS via linear array scanning (LAS) is proposed. The basic idea is to paste a mark containing a printed black continuous bar and a black block (BCBB) on the surface of a rotating cylinder, and use a linear array camera to synchronously sample the bar and blocks. For the extraction of mark edges, we propose a single edge pixel extraction method through gray gradient of row pixels based on the observation of relatively stable gray level distribution. Line scanned signals disturbed by seam error or axial offset are automatically corrected through seam compensation and axial offset correction respectively. Experimental validation of the proposed method is presented for the cylinder under static hammering, variable speed condition and steady speed condition at a scanning distance of 500 mm. Bilinear interpolation is applied to the scanned linear array images before extracting the edge features and helps improve measurement accuracy. Analyses in the time domain and frequency domain verify the effectiveness of the LAS. The average error between the RS signal obtained by LAS and the reference value is 0.1420 rpm. The correlation coefficient between the AV time-domain signal of LAS and the reference signal is up to 0.900 and the resonance frequency error in the frequency spectrum is less than 1 Hz.